Controle biológico, físico e químico de Phytophthora palmivora em plântulas de mamoeiro cv. sunrise solo - Carnaúba, Juliana Paiva (2006)
The papaya culture is extensively cultivated in the world, where Brazil meets as worldwide the producing greater. Amongst the problems main inherent to the culture, the root and fruit rots are distinguished, caused by Phytophthora palmivora. The present work had for objective to control P. palmivora in seedling of papaya cv. Sunrise solo, through methods of biological, physical and chemical control. They had been tested four Trichoderma isolated (T. koningii - T3; T. harzianum - T13; Trichoderma sp. - T152D and T. polysporum - TP) and five fungicides "in vitro" (copper oxychloride - 2; 3 e 4g/L; mancozeb - 2; 3 e 4g/L; metalaxyl + mancozeb - 2,5; 3,5 e 4g/L; thiophanate-methyl - 6; 7 e 8g/L and carbendazim - 0,5; 1,0 e 1,5mL/L) and "in vivo", as well as the solarization of the substratum in solar collectors. They had been made still, test of volatile, not volatile metabolites and hyperparasitism for the Trichoderma isolated. In the biological control "in vitro", used the plate technique, while in the in vivo control, the substratum was dealt with Trichoderma of isolated and integrated form, before the infestation of the ground. In the chemical control, the fungicides had been tested "in vitro" adding them in BDA medium, while "in vivo" the seedlings roots had been immersed during 10 minutes in the fungicides solution. The solarization of the substratum was carried during 24, 48 and 72 hours, in solar collectors of 10 and 15 cm of diameter, becoming infested itself, previously the substratum with the pathogen (40 mL of inocule with approximately 20 sporangia for mL/ vase). The Trichoderma isolated T3, T13 and TP had been most efficient in the inhibition of the growth of P. palmivora "in vitro", however, only the isolated TP produced volatile and not volatile metabolites. On the other hand, all the isolated ones had presented capacity to hyperparasite the pathogen. In the biological control "in vivo" no isolated one was capable to reduce the severity of the disease. The solarization of the substratum increased significantly the seedlings survival, when compared to the witness. It didn t have significant differences between the periods of solar exposition, however, the diameter of 15 cm presented one better efficiency, with 87% of seedlings survival. The products most efficient in the pathogen inhibition "in vitro" had been oxicloreto de cobre, mancozeb and metalaxyl + mancozeb, while "in vivo" the five fungicides had presented similar efficiency, not having significant difference between the dosages tested.